ARCHITECTURE OF INDUSTRIAL AUTOMATION SYSTEMS - Abdu Idris Omer; M.M Taleb (European Scientific Journal, ESJ, 2014)
This article is aimed to name the levels of industrial automation, describes the hierarchical structure of industrial automation systems, (what information one accept from another, what information can be given from one to another), describes essential functions of each level, and mentions the differences between automatic control and supervisory control. Moreover, the article provides an exposure to the technologies that enable operation and control of modern industrial machines and systems.